Preliminary floristic reconnaissance and nutritive evaluation of native forages of the Miranda and Nabileque subregions in the Brazilian Pantanal - Pott, Edison Beno; Pott, Arnildo; Boock, Araê (Pesquisa Agropecuaria Brasileira, 2014)
Calcium, magnesium, phosphorus, potassium, copper, iron, manganese, zinc and crude protein contents were determined in samples of native forage plants (Discolobium pulchellum, Hemarthria altissima, Hymenachne amplexicaulis, Leersia hexandra, Oryza latifolia, Paspalum hydrophilum, P. oteroi, P. pontanalis and Thevetia amazonica) collected in December/85, on eight briefly described physiognomies, on the Miranda river flood plain, near the limits between the townships of Miranda and Corumbá, Mata Grosso do Sul. Only Zn was limiting for grazing beef cattle.